Dietary Knowledge, Attitudes, and Practices of Urban and Rural Adults in Kalaburagi, India (International Journal of Food and Nutritional Sciences, 2022)
The study aimed to assess the dietary knowledge, attitudes, and practices of urban and rural adults in Kalaburagi, India. A cross-sectional survey was conducted among 600 adults, comprising 300 urban and 300 rural residents. A structured questionnaire was used to gather data on dietary knowledge, attitudes, and practices. The study found that 60% of respondents had inadequate dietary knowledge, with higher rates observed among rural residents. Most respondents (70%) had positive attitudes towards healthy eating, with urban residents exhibiting more positive attitudes than rural residents. However, only 45% of respondents reported consuming a balanced diet, and only 20% reported meeting the recommended daily intake of fruits and vegetables. Urban residents were found to have better dietary practices than rural residents. The study highlights the need for public health interventions that target improving dietary knowledge and practices in both urban and rural areas. Community-based nutrition education programs, school-based interventions, and policy changes that promote access to healthy and affordable food options could help to address the issue of inadequate dietary knowledge and poor dietary practices in Kalaburagi, India.